Female sexuality in marketing communication and effects on the millennial buying decisions in fashion industry in Nigeria - Ayodele Christopher Oniku; Anthonia Farayola Joaquim (Rajagiri Management Journal (RAMJ), 2022)
Purpose - The study aims to examine female sexuality in marketing communications and how it shapes the millennial buying decisions in the fashion industry. The focus of the study is to connect fashion industry and marketing communication to understand how female sexuality influence buying behaviours and decisions of the millennial. Design/methodology/approach - The study was underpinned by the dimensions of skin colour, brand image and market share in sexual appealing marketing communication, and the millennial in the study comprises youths between the age of 21and 40 years and demographically defined by Wells and Guber (1966) as bachelors, Full nests 1 and 2. Multistage stage sampling was used with a structured questionnaire. Findings - Findings show that youths, 2019 buying decisions and behaviours are strategically influenced by different manifestations of female sexuality in the context of the study and equally affect market share and patronage. Research limitations/implications - The study shows what shapes the marketing communication strategies of the rising fashion industry but is limited to the millennial buying decisions and not the larger fashion industry consumers. Practical implications - The needs for fashion industry to understand the influence of increasing use of female sexuality in marketing communication on male and female consumers and the effects on their respective buying behaviours is strategic to the industry as shown in the study. Social implications - Female sexuality in marketing communication is strategic to fashion industry in today's market among youths. Originality/value - The millennial constitutes a larger percentage of the developing economy market with rising income thus the need to understand their buying behaviours in the fashion industry.
Keywords: 650; Brand image; Fashion; Female sexuality; Marketing communication; Millennial; Patronage